2020
DOI: 10.1126/sciadv.aaz4764
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of cellular identity–associated H3K4me3 breadth by the COMPASS family

Abstract: Set1A and Set1B, two members of the COMPASS family of methyltransferases that methylate the histone H3 lysine 4 (H3K4) residue, have been accredited as primary depositors of global H3K4 trimethylation (H3K4me3) in mammalian cells. Our previous studies in mouse embryonic stem cells (ESCs) demonstrated that deleting the enzymatic SET domain of Set1A does not perturb bulk H3K4me3, indicating possible compensatory roles played by other COMPASS methyltransferases. Here, we generated a series of ESC lines harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 87 publications
(129 reference statements)
4
27
3
Order By: Relevance
“…These data may suggest that H3K4 KTM's other than Setd1b are essential to ensure the sufficient expression of genes important for basal cellular processes in neurons, while Setd1 enables to preeminent expression of neuronal identity genes. This view is in line with a recent study in mouse embryonic stem cells in which Setd1b was associated with the expression of highly expressed genes that exhibit a broad H3K4me3 peak, while Kmt2b was linked to the expression of genes with narrow H3K4me3 peaks (Sze et al, 2020). Interestingly, this study suggested a functional redundancy of Setd1b and Setd1a.…”
Section: Discussionsupporting
confidence: 91%
“…These data may suggest that H3K4 KTM's other than Setd1b are essential to ensure the sufficient expression of genes important for basal cellular processes in neurons, while Setd1 enables to preeminent expression of neuronal identity genes. This view is in line with a recent study in mouse embryonic stem cells in which Setd1b was associated with the expression of highly expressed genes that exhibit a broad H3K4me3 peak, while Kmt2b was linked to the expression of genes with narrow H3K4me3 peaks (Sze et al, 2020). Interestingly, this study suggested a functional redundancy of Setd1b and Setd1a.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is a confusion with the nomenclature between MLL2 and MLL4 [ 7 , 17 ]. The current literature indicates that KMT2F and KMT2G complexes catalyze all three states of methylation and are responsible for most of H3K4 trimethylation including that at the broad H3K4me3 domains, while KMT2A-D produces mono- and/or di-methyl H3K4 [ 17 22 ] (Table 1 ). In one of these studies, H3K4 methyl forms were determined by mass spectrometry [ 19 ], circumventing the issue of frequent cross-reactivity of many H3K4me3 antibodies with H3K4me1 or H3K4me2 [ 23 ].…”
Section: H3k4me3 Writers Erasers and Readersmentioning
confidence: 99%
“…46 Interestingly, a recent study found that SETD1A/B complexes establish broad H3K4me3 peaks at highly expressed genes while MLL2 establishes narrow H3K4me3 peaks at promoter regions of lowly transcribed genes to maintain cell identity of embryonic stem cells (ESCs). 47 Intriguingly, the same authors demonstrated that in the absence of SETD1A/B in ESCs, H3K4me3 is maintained by MLL2, suggesting that these enzymes share some overlapping functions. The idea was further confirmed recently in mouse oocyte.…”
Section: Compass Complexes Regulating Histone H3k4 Tri-methylationmentioning
confidence: 93%
“…MLL3/MLL4 mainly catalyze H3K4me1 at enhancer regions, SETD1A/B maintain global H3K4me3 and MLL1/MLL2 deposit the same modification in a locus‐specific manner 46 . Interestingly, a recent study found that SETD1A/B complexes establish broad H3K4me3 peaks at highly expressed genes while MLL2 establishes narrow H3K4me3 peaks at promoter regions of lowly transcribed genes to maintain cell identity of embryonic stem cells (ESCs) 47 …”
Section: Cfp1: a Regulatory Protein Found In Multiple Protein Complexesmentioning
confidence: 99%